Local citizen participation: reflections from the spanish literature on the subject - Palassi, Marcia Prezotti; Silva, Alfredo Rodrigues Leite da; Silveira, Rogerio Zanon da (Revista de Administração da UFSM, 2017)
This theoretical essay is oriented by the following question: How can the Spanish experience obtained from theoretical contributions on the topic of citizen participation contribute to the understanding of the articulation of the popular role in the conduct of public and local social policies? The goal is to identify and discuss contributions of the Spanish experience to the development of local citizen participation theme. The results show a profusion of ideas that inhabit different visions of what comes to be participating as a citizen in a given locality. These ideas allow you to associate local citizen participation: change of social reality; integration of participation in management; local cultural-historical values and minority expressions; horizontal relations and reliable; on completion of the representative system; waking the ideas of domination and exclusion that can permeate it; his practice of individual and collective form; precedence types of management and personal modes of management; and planning, organization and budget definition for it to work.